Local temperature measurement in TEM by parallel beam electron diffraction - Niekiel, Florian; Kraschewski, Simon; Müller, Julian; Butz, Benjamin; Spiecker, Erdmann (Ultramicroscopy, 2017)
With the recent advances in instrumentation pushing the limits of in situ transmission electron microscopy, the question of local sample temperature comes into focus again. In this work the applicability of parallel beam electron diffraction to locally measure and monitor the sample temperature in TEM is assessed, with applications for in situ heating experiments in mind. With Au nanoparticles applied to the sample surface, temperature is measured in the range from RT to 890°C by evaluating the change in scattering angle upon thermal expansion. Repeated measurements at constant temperature reveal a statistical precision of the method as good as 2.8K. The applicability to locally measure the temperature is demonstrated mapping the temperature gradient across a heating chip. Owing to instantaneous response of thermal expansion to temperature changes, the method is well suited for monitoring even quick temperature changes, as demonstrated by quenching experiments. In order to enable extensive in situ studies, an evaluation method capable of processing large datasets with high precision is developed. Beam parallelity is identified as crucial experimental prerequisite and a routine is established, optimizing the microscope alignment in terms of beam parallelity. Apart from establishing a procedure for local temperature measurement, the present work demonstrates the unique capabilities of MEMS-based in situ heating equipment.
Keywords: Beam parallelity; In situ microscopy; Metallic nanoparticles; Microscope alignment; Temperature measurement; Transmission electron microscopy

Silver-induced layer exchange and crystallization of a-Si films investigated using in situ scanning transmission electron microscopy - Yadav, Surbhi; Birajdar, B. I.; Kraschewski, Simon; Apeleo Zubiri, Benjamin; Antesberger, T.; Stutzmann, M.; Spiecker, Erdmann (Journal of Applied Physics, 2024)
Ag-induced crystallization and layer exchange (AgILE) in a stack of amorphous Si/Ag/quartz substrate has been investigated using optical microscopy, scanning electron microscopy, transmission electron microscopy (TEM), scanning TEM-high angle annular dark field (STEM-HAADF) imaging, and electron tomography, covering length scales from a few tens of micrometers to a few tens of nanometers. The size of Ag grains in the underlying as-deposited Ag film varied from ∼10 to 500 nm. The following processes could be discerned using in situ heating of plan-view samples at 500 °C in STEM: (i) AgILE propagation preferentially along regions of small Ag grains, (ii) formation of pushed-up Ag in the vicinity of AgILE reaction cells, (iii) migration and agglomeration of pushed-up Ag on small and large Ag grains, which tend to inhibit AgILE and promote dendricity, and (iv) dispersion of pushed-up Ag, which tend to reduce dendricity. The resulting dendricity was largely confined to the peripheral regions of the impinging reaction cells and decreased with annealing time. In contrast, dendricity due to AgILE and crystallization at 550 °C is stable and extends right from the center to the periphery of the reaction cells. The microscopic mechanism of AgILE and, in particular, the effect of annealing temperature is investigated. The results are discussed in the light of existing literature and compared with Al-induced layer exchange. Annealing at temperature equal to or slightly less than 500 °C is found to be necessary in the case of AgILE to avoid dendricity and to obtain a continuous Si layer with large Si grains.
CRIS-Team Scopus Importer:2024-09-13

Texture evolution and microstructural changes during solid-state dewetting: A correlative study by complementary in situ TEM techniques - Niekiel, Florian; Kraschewski, Simon; Schweizer, Peter; Butz, Benjamin; Spiecker, Erdmann (Acta Materialia, 2016)
The transition of a thin film into an energetically favorable set of particles at temperatures below the melting point of the bulk material is known as solid-state dewetting. In this work the dewetting behavior of 16 nm thick discontinuous Au thin films on amorphous silicon nitride membranes is quantitatively studied by complementary in situ transmission electron microscopy techniques taking advantage of the unique capabilities of a chip-based heating system. The combination of dedicated imaging and diffraction techniques is used to investigate the interplay of grain growth and texture evolution with the process of dewetting. The results show an initial coarsening of the microstructure preceding the other processes. Texture evolution is highly correlated to material retraction and agglomeration during the following dewetting process. In-plane grain rotation has been observed, acting as an additional mechanism for orientation changes. From a methodological perspective this work demonstrates the capabilities of today's transmission electron microscopy in combination with state-of-the-art in situ instrumentation. In particular the combination of complementary information from different dedicated techniques in one and the same setup is demonstrated to be highly beneficial. (C) 2016 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Solid-state dewetting; Thin films; Texture; Grain growth; Grain rotation

The process of solid-state dewetting of Au thin films studied by in situ scanning transmission electron microscopy - Niekiel, Florian; Schweizer, Peter; Kraschewski, Simon; Butz, Benjamin; Spiecker, Erdmann (Acta Materialia, 2015)
Solid-state dewetting describes the transformation of thin films into a set of particles or droplets at temperatures well below the melting temperature of the bulk. In this work in situ scanning transmission electron microscopy has been used to study the dewetting behavior of discontinuous Au thin films (15 nm and 22 nm thick) on amorphous silicon nitride membranes at temperatures ranging from 300 °C to 600 °C. The combination of microscopic and statistical information enabled not only the qualitative discussion of the observed processes but also the quantification of the kinetics as well as the development of a model of the underlying morphological mechanism. A model-free master curve approach to the temporal evolution of the covered area at different temperatures is used to determine the activation energy of dewetting (1.04±0.14eV for the 15 nm thick film). A closer inspection reveals a multiple power law behavior, which is discussed in the frame of depercolation. Retraction of finger-like structures is found to be the dominant morphological mechanism based on the observed linear relationship between covered area and boundary length.
Keywords: Image analysis; Morphology; Solid-state dewetting; Temporal evolution; Thin films